The Relationship Between Sitting Duration and the Incidence of Low Back Pain Among Bus Drivers - Nita, Charisma Nirmala; Kusumaningayu, Warih Anjari Dyah; Diyono (FISIO MU: Physiotherapy Evidences, 2026)
Background: The job of a bus driver requires sitting for long periods in a static position within a confined workspace. This condition poses a risk of musculoskeletal disorders, especially low back pain (LBP), which is caused by high biomechanical stress on the spine. LBP is one of the most common complaints among informal sector workers such as drivers, who often neglect occupational safety and health factors. This can occur due to prolonged sitting without breaks and non-ergonomic sitting positions, which may lead to muscle fatigue and lower back pain. Research Objective: This study aimed to determine the relationship between sitting duration and the incidence of low back pain among bus drivers. Methods: This research was an observational study with a correlational approach. A sample of 91 respondents was selected using random sampling from a total population of 118 bus drivers at the Giri Adipura Terminal, Wonogiri. Data were collected using questionnaires and lower back pain examinations with the Lasegue Test and palpation. The data were analyzed using the Spearman test with SPSS version 25. Results: The majority of respondents (85.7%) had a sitting duration of 5–8 hours per day. The Spearman test results showed that there was no significant relationship between sitting duration and the incidence of low back pain (p-value = 0.052; p > 0.05). This is because the drivers demonstrated high awareness of occupational health by regularly performing stretching exercises and maintaining proper posture while driving. In addition, the company paid attention to driver comfort and occupational health by providing ergonomic seats and adequate rest schedules. These facilities help reduce biomechanical stress on the spine and support a healthier working condition for drivers. Conclusion: This study shows that there is no significant relationship between sitting duration and the incidence of low back pain among bus drivers. Keywords: low back pain, sitting duration, bus drivers